2021
DOI: 10.3390/ma14216541
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Use of Graphene Oxide and Silica Fume in Cement-Based Composites

Abstract: Incorporation of graphene oxide (GO) and silica fume (SF) to cement composites enhances their mechanical properties if suitable proportional amounts of GO and SF are used. This study presents a simplified approach to determine experimentally the optimum GO and SF contents that should be added to the cementitious mixture to obtain a proper and stable dispersion of GO sheets within the cement matrix. Composite mortar specimens with different GO and SF contents were designed and tested under flexural and compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…[ 49 ] When composited with GO and SF, the incorporation of GO made the pozzolanic reaction of SF deeper and enhanced the compactness of the matrix, which led to better frost resistance of the specimens. [ 46 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 49 ] When composited with GO and SF, the incorporation of GO made the pozzolanic reaction of SF deeper and enhanced the compactness of the matrix, which led to better frost resistance of the specimens. [ 46 ]…”
Section: Resultsmentioning
confidence: 99%
“…[44,45] When composited with SF and GO, GO makes the reaction between SF and calcium hydroxide more sufficient, and both of them play a regulatory role in the hydration and crystallization of cement minerals, thus improving the compactness of the matrix. [46] 3.6. Frost Resistance…”
Section: Impermeabilitymentioning
confidence: 99%
“…Additionally, after 28 days of curing, the compressive strength and exural strength showed increases of 41% and 16%, respectively. It was reported by Abdullah and co-worker [34] reported that the compressive strength and exural strength increased by 31% and 18% with the addition of 0.03% of GO with silica fume. From another experimental study [35] it was indicated that the addition of 0.03% of GO into cement composite increased the compressive strength, exural strength, and tensile strength by 38.9%, 60.7%, and 78.6% respectively.…”
Section: Introductionmentioning
confidence: 82%
“…It was concluded by Zhao and coworker [54] deduced that adding 0.022% GO at different water-cement ratios increased the compressive strength of cement composites by 16.31-25.60%. According to Abdullah team [34], the addition of a modest amount of GO, such as 0.05% by weight of cement with 7% silica fume, resulted in a 29% increase in compressive strength after 28 days compared to the control. It was observed that as the concentration of GO increased at different ages, the compressive strength of concrete mixes gradually increased.…”
Section: Compressive Strengthmentioning
confidence: 99%